ANALISIS TINDAK TUTUR DALAM INTERAKSI MASYARAKAT PEDESAAN DAN PEKOTAAN: ANALYSIS OF SPEECH ACTS IN RURAL AND URBAN INTERACTIONS - Melinda, Nur; Azis; Nurhusna (Journal of Applied Linguistics and Literature, 2024)
This research aims to describe the comparison of the form and function of speech acts in the interaction of rural and urban communities. This research is a qualitative research, the data source is rural community in Marusu Sub-district and urban community in Panakkukang Sub-district. The data collection techniques used are observation, documentation, and note-taking techniques. Data analysis techniques in this research are data reduction, data presentation, and conclusion drawing. The results showed that the comparison of speech act forms in rural communities and urban communities both locution, illocution, and perlocution speech acts are similar between the two. Comparison of speech act functions in rural and urban communities includes commissive speech acts whose data are only found in rural communities, but the data of commissive speech act functions are not found in urban communities.